Underpricing and Entrepreneurial Wealth Losses in IPOs: Theory and Evidence - Habib, Michel A.; Ljungqvist, Alexander P. (Review of Financial Studies, 2001)
We model owners as solving a multidimensional problem when taking their firms public. Owners can affect the level of underpricing through the choices they make in promoting an issue, such as which underwriter to hire or on what exchange to list. The benefits of reducing underpricing in this way depend on the owners' participation in the offering and the magnitude of the dilution they suffer on retained shares. We argue that the extent to which owners trade off underpricing and promotion is determined by the minimization of their wealth losses. Evidence from a sample of U.S. initial public offering confirms our empirical predictions.